Two-electrode electrochemical impedance spectroscopy at polymer/oxide interfaces - Golebiowska, Sandra Alicja; Meinderink, Dennis; Ebbert, Christoph; Kollmann, Sabrina; Neßlinger, Vanessa; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

Corrosion fatigue behavior of nanoparticle modified iron processed by electron powder bed fusion - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Frenck, Johanna-Maria; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Due to its excellent biocompatibility, pure iron is a very promising implant material, but often features corrosion rates that are too low. Using additive manufacturing and modified powders the microstructure and, thus, the material properties, e.g., the corrosion properties, can be tailored for specific applications. Within the scope of this study, pure iron powder was modified with different amounts of CeO 2 or Fe 2 O 3 nanoparticles and subsequently processed by Electron Beam Powder Bed Fusion (PBF-EB/M). The corrosion-fatigue behavior of CeO 2 and Fe 2 O 3 modified iron was investigated using rotation bending tests under the influence of simulated body fluid (m-SBF). While the modification using Fe 2 O 3 showed reduced fatigue and corrosion-fatigue strengths, it could be demonstrated that the modification with CeO 2 is characterized by improved fatigue properties. The superior fatigue properties in air are attributed to the positive impact of dispersion strengthening. Additionally, an increased degradation rate compared to pure iron could be observed, eventually promoting an earlier failure of the specimens in the corrosion fatigue tests.

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung unter Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson; Meinderink, Dennis; Golebiowska, Sandra; Rieker, Florian; Ebbert, Christoph; Grundmeier, Guido

Oxide Modified Iron in Electron Beam Powder Bed Fusion—From Processability to Corrosion Properties - Torrent, Christof J. J.; Krooß, Philipp; Huang, Jingyuan; Voigt, Markus; Ebbert, Christoph; Knust, Steffen; Grundmeier, Guido; Niendorf, Thomas (Alloys)
Additive manufacturing (AM) processes are not solely used where maximum design freedom meets low lot sizes. Direct microstructure design and topology optimization can be realized concomitantly during processing by adjusting the geometry, the material composition, and the solidification behavior of the material considered. However, when complex specific requirements have to be met, a targeted part design is highly challenging. In the field of biodegradable implant surgery, a cytocompatible material of an application-adapted shape has to be characterized by a specific degradation behavior and reliably predictable mechanical properties. For instance, small amounts of oxides can have a significant effect on microstructural development, thus likewise affecting the strength and corrosion behavior of the processed material. In the present study, biocompatible pure Fe was processed using electron powder bed fusion (E-PBF). Two different modifications of the Fe were processed by incorporating Fe oxide and Ce oxide in different proportions in order to assess their impact on the microstructural evolution, the mechanical response and the corrosion behavior. The quasistatic mechanical and chemical properties were analyzed and correlated with the final microstructural appearance.

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung und Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson; Meinderink, Dennis; Koch, Leon; Ebbert, Christoph; Grundmeier, Guido

Surface inoculation of aluminium powders for additive manufacturing of Al-7075 alloys - Vieth, P.; Voigt, Markus; Ebbert, Christoph; Milkereit, B.; Zhuravlev, E.; Yang, B.; Keßler, O.; Grundmeier, Guido (Procedia CIRP)

Influence of the Surface and Heat Treatment on the Bond Strength of Galvanized Steel/Aluminum Composites Joined by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Grothe, Richard; Schmidt, Hans Christian; Hordych, Illia; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
The influence of a chemical or mechanical surface modification followed by different post-heat treatments on the bond strength of galvanized steel/ aluminum composites is studied. An incremental rolling process is used for joint formation based on plastic deformation. The morphology, the chemical state of the modified surfaces as well as the cross-section, and local potential distribution of the welded zone is characterized by different microscopic and spectroscopic methods. The stability of the joint is analyzed by a shear-force test in combination with microscopic failure analysis. A clear correlation between pre/post-treatment and the joint strength is observed.

Molecular Engineering of Aluminum-Copper Interfaces for Joining by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Voigt, Markus; Schmidt, Hans Christian; Rodman, Dmytro; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
Interface modification based on ultra-thin mercapto-propyl(trimethoxy) silane (MPTMS) films is shown to promote joining of copper and aluminum by plastic deformation followed by a heat treatment. The surface morphology and the surface chemistry of the metal substrates were analyzed by means of FE-SEM, XPS, and FT-IRRAS. The spectroscopic data show that the MPTMS film is crosslinked via Si-O-Si bonds and that stable Cu-S and Si-O-Al interfacial bonds are formed. The shear-force tests of the joints led to force displacement curves that are characteristic for a covalently bonded interface. Complementary cross sectional SEM and EDS analysis of the joint proved that a defect-free interface was formed without any measureable interdiffusion of metals across the interface or cracking of an oxide films.

Joining with electrochemical support (ECUF): Cold pressure welding of copper - Ebbert, Christoph; Schmidt, H. C.; Rodman, D.; Nuernberger, F.; Homberg, W.; Maier, H. J.; Grundmeier, Guido (JOURNAL OF MATERIALS PROCESSING TECHNOLOGY)
Joining metals using electrochemical support (ECUF) is a new process for cold pressure welding sheets and parts. This new process is based on an electrochemical in-line surface treatment followed by incremental pilger rolling. The ECUF process intends to cold pressure weld materials under optimized conditions. Oxide layers on metal surfaces are known to inhibit the formation of cold pressure welds. The in-line electrochemical treatment will be used to remove these surface oxides for specific engineering metals and alloys. Hence, an improved pressure weld formation at lower forces and smaller reduction ratios is expected for the electrochemically treated surfaces. Using a more flexible pressure welding process, the number of applications could be greatly improved. First tests with copper were performed to analyse the efficiency of the proposed electrochemical surface treatments. Two electrochemical treatments, the cathodic oxide-reduction and cyclovoltammetric oxide-reduction, were compared with conventional treatments (degreasing and scratch brushing) regarding their influence on the cold pressure welding process of copper. The weld strength of lap welds has been investigated as well as the necessary reduction threshold to form a weld. It was found that the electrochemical oxide reduction resulted in higher weld strength. The results of scanning electron microscopy (SEM) and energy dispersive analysis of X-rays (EDX) indicate that surface oxides were successfully removed by the electrochemical surface treatments. (C) 2014 Elsevier B.V. All rights reserved.

Spectroelectrochemical and morphological studies of the ageing of silver nanoparticles embedded in ultra-thin perfluorinated sputter deposited films - Ebbert, Christoph; Alissawi, N.; Somsen, C.; Eggeler, G.; Strunskus, T.; Faupel, F.; Grundmeier, Guido (Thin Solid Films)

Toward a microscopic understanding of the calcium-silicate-hydrates/water interface - Ebbert, Christoph; Grundmeier, Guido; Buitkamp, Nadine; Kroeger, Alexander; Messerschmidt, Florian; Thissen, Peter (APPLIED SURFACE SCIENCE)
Calcium-Silicate-Hydrates (C-S-H) are the main binding phases in most concrete which is the primarily used composite construction material in the world. However, a big lack is cleaving between the actual knowledge about C-S-H, compared to what could be reached using state-of-the-art technologies of modern research. In this article, the formation of a C-S-H phase on a native oxide covered silicon wafer is investigated by means of in-situ attenuated total reflection infrared (ATR-IR) and ex-situ surface-enhanced Raman spectroscopy (SERS). The total thickness of the C-S-H phase is determined by X-ray photoelectron spectroscopy (XPS) to be 3 nm. The formation appears to be reversible depending on the environment pH value and can be performed at room temperature. Based on density functional theory (DFT) calculations, it is shown that the C-S-H phase in the presence of water will change its chemical composition in order to reach the thermodynamic ground state of the system. This change is achieved by a metal-proton exchange reaction. The stoichiometry of these metal-proton exchange reactions is nearly independent of the environment pH value. Electrokinetic measurements yield isoelectric points of 2.0 and 2.6 for the native oxide covered silicon wafer (SiO2) and the C-S-H phase. This is consistent with a predominance of Si-O sites at the C-S-H/water interface. (C) 2013 Elsevier B. V. All rights reserved.

Plasma-polymerized HMDSO coatings to adjust the silver ion release properties of Ag/polymer nanocomposites - Alissawi, N.; Peter, T.; Strunskus, T.; Ebbert, Christoph; Grundmeier, Guido; Faupel, F. (JOURNAL OF NANOPARTICLE RESEARCH)
In the current work, we study the silver ion release potential and the water uptake through a SiOxCyHz-polymer which is grown from the precursor hexamethyldisiloxane (HMDSO) in radiofrequency (RF) plasma. These layers were deposited on top of two dimensional (2D) ensembles of silver nanoparticles (AgNPs) with nominal thickness of 2 nm on a 20 nm RF-sputtered polytetrafluoroethylene (PTFE) thin film. The composition of the plasma-polymerized HMDSO barriers was varied by changing the oxygen flow during the polymerization process and their thickness was varied as well. Morphology and optical properties of the nanocomposites were investigated using transmission electron microscopy (TEM) and UV-Visible spectroscopy (UV-Vis), respectively. The concentration of the silver ions released from the nanocomposites after immersion in water for several time intervals was measured using inductively coupled plasma mass spectrometry (ICP-MS). Contact angle analysis and electrochemical impedance spectroscopy (EIS) measurements were also performed and results show a strong dependence of the coatings properties and their water uptake on the oxygen content in the coating films and their thickness. Plasma polymerization with increasing the oxygen flow leads to the formation of more hydrophilic thin films with a higher Ag ion release potential. Increasing the thickness of the coatings reduced the amount of the released ions and the rate of the release process was slowed down. This indicates that by tailoring the structure and the thickness of the plasma-polymerized coating films, one can tune the silver ion release properties of Ag/polymer nanocomposites.

PM-IRRAS studies of the adsorption and stability of organophosphonate monolayers on passivated NiTi surfaces - Maxisch, M.; Ebbert, Christoph; Torun, B.; Fink, N.; de los Arcos, T.; Lackmann, J.; Maier, H. J.; Grundmeier, Guido (APPLIED SURFACE SCIENCE)
Alkylphosphonic acids of different alkyl chain lengths were adsorbed on electrochemically polished NiTi surfaces from ethanolic solutions. The electropolishing process led to passive films mainly composed of Ti-oxyhydroxide. The surface showed nanoscopic etching pits with a depths of about 2 nm and a diameter of about 20 nm. The interfacial binding mechanism of the phosphonic acid group to the oxyhydroxide surface and the ordering of the monolayer were spectroscopically analysed by means of infrared reflection absorption FTIR-spectroscopy with (PM-IRRAS) and without (IRRAS) photoelastic modulation. The comparison of IRRAS and PM-IRRAS data of the long chain octadecylphosphonic acid monolayer proved that the binding mechanism of the phosphonic acid group to the oxyhydroxide surface is based on a mono-or bidentate bond, which is not stable in the presence of high water activities. An alkyl chain length of 17 CH2 groups is required for the formation of self-assembled monolayers, which are stable in aqueous environments. These long chain aliphatic organophosphonic acid monolayers were shown to inhibit anodic and cathodic surface reactions. (C) 2010 Elsevier B.V. All rights reserved.